Wedge‐Like Microstructure of Al2O3/i‐Ti3C2Tx Electrode with “Nano‐Pumping” Effect for Boosting Ion Diffusion and Electrochemical Defluoridation - Junce Wang; Jinfeng Chen; Ningning Liu; Jingjing Lei; Hong‐Wen Gao; Fei Yu; Fanghui Pan; Jie Ma (Advanced Science)
Abstract Controlled synthesis and regulation of 2D nanomaterials with sufficient active sites are promising in electrochemical fluorine capture, but simultaneously achieving rapid rates and efficient activity of intercalation materials remains challengs. Herein, an integrated strategy of micro‐regulation interlayer space and in situ modification of MXenes is proposed to enhance ion storage kinetics. The wedge‐like microstructure of aluminum oxide/incomplete‐Ti3C2Tx MXene (Al2O3/i‐Ti3C2 Tx) is constructed by incomplete etching MAX and in situ derivation of A‐layer element, in which the sub‐nanoscale interlayer space is conducive to the small size ions intercalation, and the formation of “nanopump‐like” effect boosted the ions diffusion. As evidenced by simulation calculations, Al2O3 nanoparticles not only shorten the migration distance of electrons/hydrated ions in interlayers but also contribute a lower adsorption energy barrier, bringing excellent capture kinetics and stability. Benefiting from the interfacial conversion‐intercalation pseudocapacitance, such electrode is endowed with a high defluoridation capacity (69.9 mg g−1 at 1.6V) and an outstanding instantaneous adsorption rate (9.51 mg g−1 min−1), and shows satisfactory stability in more than 200 cycles. The physicochemical coupling strategy opens a novel approach to optimizing the interlayer structure and in situ modification interface of MXene, which also provids a universal idea for efficient capture of varisized ions of intercalation materials.